Hyperforin Accumulates in the Translucent Glands of Hypericum perforatum - Soelberg, Jens (Oxford University Press, 2007)
BACKGROUND AND AIMS: Hypericum perforatum contains the therapeutically important compounds hypericin and hyperforin. Hypericin is known to accumulate in the dark glands. This investigation aimed to determine the accumulation site of hyperforin. METHODS: Dark and translucent glands as well as non-secretory tissue in leaves were manually isolated under the microscope. Hyperforin content was quantified by UV HPLC. Secretory structures were surveyed anatomically. KEY RESULTS: The hyperforin content of intact leaves was found to be about 3 mg g(−1) fresh tissue, whereas a content of about 7 mg g(−1) fresh material was found in isolated translucent glands. Hyperforin was found only to occur in minute amounts in dark glands (approx. 0·4 mg g(−1) fresh tissue). In non-secretory tissue no hyperforin was detected. CONCLUSIONS: The accumulation of hyperforin detected in the translucent glands supports the proposed hypothesis that hyperforin is synthesized by the same biosynthetic machinery as monoterpenes in the chloroplasts of cells delimiting the gland.